PELATIHAN PENYUSUNAN E-MODUL PEMBELAJARAN UNTUK MENINGKATKAN PENGETAHUAN BAGI GURU DI SMA MUHAMMADIYAH ACEH TENGAH - Anggra, Bobbi Noptin; Khoiri, M; Setiawan, Rizky Bintang; Ningsih, Sulistio; Maulya, Ranti; Lestaria, Evi (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Education plays a crucial role in supporting the learning process. For students, the learning process is a real game changer in enhancing their intellectual and competency. The increasingly massive digital development and the widespread use of AI in all fields present challenges for educators (teachers) to adapt to these conditions. The role of evolving technology has strengthened the academic atmosphere, therefore teachers must have greater strength in navigating technology so that it can be utilized to support the current and future learning process. Muhammadiyah High School, Central Aceh, is one of the private religious schools located in the Central Aceh region. The curriculum implemented at Muhammadiyah High School, Central Aceh, uses the Merdeka Belajar curriculum. The implementation of this curriculum requires the support of engaging e-modules that can strengthen students' learning knowledge, making it more innovative and engaging. Therefore, teachers are expected to be able to develop engaging open tools, one of which is the creation of innovative e-modules. The result of this training activity is the development of teachers' abilities and knowledge in creating good e-modules that can be utilized in the learning process by students at Muhammadiyah High School, Central Aceh.